(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Using first-principles method the charging energy has been calculated; of the smallest single electron transistor (SET) consisting of only two carbon atoms while operating in coulumb blockade regime. The ethyne (C2H2) molecule is acting like a quantum dot (with discrete energy levels) and is weakly coupled to the gold electrodes (continuum). The quantum effects are significant and the conduction of current takes place through incoherent method via electron tunneling. The electronic levels of the molecule determine the electron transport properties. The molecule may be in several charged states from +2 to -2. It has been observed that the HOMO-LUMO gap is strongly reduced in solid state environment with metallic electrodes, as compared to the vacuum. This reduction is attributed to the image charges generated in the source and drain electrodes. This results in strong localization of charges in the molecule, a phenomenon addressed earlier. The charging energy has been calculated in vacuum and in SET environment. The interaction between molecule and the electrodes is treated self-consistently through Poisson equation. The charge stability diagram of the smallest molecular SET has been obtained.